Improving Students’ Learning Participation through the Snowball Throwing Learning Model - Sintia Martogi Hutapea; Herlian Pasha; Asep Ikbal; Ali Sunarno (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2025)
This classroom action research aims to overcome the problem of low student participation in Civics learning, specifically on the material of Citizens' Rights and Obligations in class X-1 of SMAN 5 Palangka Raya. The study applied the Snowball Throwing cooperative learning model to describe its implementation and analyze its impact on increasing student participation. The research method used was Classroom Action Research with the Kemmis & McTaggart model, conducted in one cycle involving 42 students. Data were collected through observation and documentation. The results showed that the implementation of the Snowball Throwing model was carried out effectively with a high level of success. Furthermore, there was a significant increase in all indicators of student participation, including activeness in asking questions, answering questions, group discussion, expressing opinions, and completing tasks on time, with an average increase of 23.4%. It was concluded that the Snowball Throwing model is an effective innovative solution to increase student participation and create a dynamic and interactive Civics learning atmosphere.